Rita Devi’s farming revival through Small Farmers Large Field model in Bihar - Janakiraman, Deepa (CGIAR, 2024)
This is story about Rita Devi, a 47-year-old farmer from Bihar, is among the 103 innovative farmers demonstrating new ways to tackle agricultural challenges through the Small Farmers Large Fields project, implemented by Transforming Agrifood Systems in South Asia (TAFSSA) in collaboration with the International Potato Center (CIP).